ANALISIS DESAIN BRACKET YAW DAMPER PADA PENGEMBANGAN BOGIE KERETA API JARAK JAUH UNTUK KECEPATAN 160 KM/JAM DENGAN METODE FEA: DESIGN ANALYSIS OF THE YAW DAMPER BRACKET IN THE DEVELOPMENT BOGIE OF LONGDISTANCE TRAIN FOR 160 KM/H SPEED USING THE FEA - Bachrul Eko Budi Santoso; Saiful; Deny (Mechanical Engineering Department Polinema Kediri, 2025)
PT KAI (Persero) requested PT INKA (Persero) to increase the operational speed of passenger trains from 120 km/h to 160 km/h to enhance efficiency and meet mass transportation demands. A key component affecting stability is the yaw damper bracket, which absorbs lateral vibrations between the bogie and carbody. This study analyzes and optimizes the bracket’s structural strength using FEA in ANSYS Workbench. The material used is SM490A steel, chosen for its high yield strength and deformation resistance. Two models were evaluated: the initial design and a topology-optimized design. Results show the bracket’s mass was reduced from 13.36 kg to 9.61 kg, improving weight efficiency by 28%. Although stress increased from 124.12 MPa to 145.05 MPa, the final design maintains a safety factor of 2.2405, remaining within safe limits. The optimized bracket is suitable for use in high-speed train structures.